Geographic variation in quantitative skull traits and systematic of southern populations of the leaf-eared mice of the Phyllotis xanthopygus complex (Cricetidae, Phyllotini) in southern South America - Teta, Pablo; Jayat, J. Pablo; Lanzone, Cecilia; Ojeda, Agustina (Zootaxa, 2018)
The leaf-eared mice of the genus Phyllotis (Cricetidae, Phyllotini) encompasses at least 20 species of medium-sized Neotropical rodents mostly distributed throughout the Andean region. Its limits and contents were reviewed by several authors, based both on morphological and molecular data. However, no integrative approaches were conducted based on large samples of individuals with a wide geographical coverage. The purposes of this paper are: (i) to evaluate species limits; and (ii) to test the congruence between molecular and quantitative morphological evidences within the Phyllotis xanthopygus complex in southern South America. Our results questioned the specific status of P. bonariensis, a geographically isolated form that was either considered as a valid species or as a synonym of P. xanthopygus. Quantitative morphological (size and shape of the skull) and molecular data linked P. bonariensis with populations from central Argentina traditionally referred as P. xanthopygus vaccarum. Individuals belonging to populations from southern Argentina and Chile (P. x. xanthopygus) were remarkably homogeneous in their skull morphology, showing a subtle to non-existent differentiation from those of north-central and west-central Argentina referred to P. x. vaccarum. We found some incongruence between groups inferred from morphological (this work) and mitochondrial DNA results of previous studies. This is the case of the north-central and west-central populations, where morphological traits do not show the strong differentiation detected by molecular characters. Our results highlight the need for integrative taxonomic studies, not only to delimitate taxonomic units but also for a better and more comprehensive understanding of population variability and differentiation.